Pengaruh Atmosfer Toko, Promosi Penjualan, dan Interaksi Antara Karyawan Toko dengan Pembeli terhadap Keputusan Impulse Buying di Carrefour Hypermarket - Pradipta, I Ngurah Made Aditya Wiara; Rastini, Ni Made (E-Jurnal Manajemen; Vol 3 No 8 (2014), 2014)
The purpose of this study was to determine the effect of atmospheric stores, sales promotion, and the interaction between the employees of the store with the buyer against impulse buying decisions in Carrefour Hypermarket in Denpasar. This research was conducted in the city of Denpasar, the samples taken were 105 people with purposive sampling method. Data was collected through questionnaires using a 5-point Likert scale to measure 15 indicators. The analysis technique used is multiple linear regression. These results indicate that each variable atmospheric stores, sales promotion, and the interaction between employees and shoppers positive and significant effect on impulse buying decisions. This suggests that the atmosphere stores, sales promotion, and the interaction between employees and shoppers can increase impulse buying decisions.
Keywords: Atmospheric Stores, Sales Promotion, Interaction Between Employee Store With Buyers, Impulse Buying